A legitimidade das entidades associativas para a tutela jurisdicional coletiva - Costa, Letícia Zuccolo Paschoal da (2013)
The study of association standing to class jurisdiction and adjudication starts from the Federal Constitution and reaches several federal statutes that rule this matter. Starts, also, from the acknowledgment that class jurisdiction is necessary in order to ameliorate access to justice. Unequivocally, Brazilian law system is one of the most evolved on what concerns the creation of mechanisms to class jurisdiction and, as such, there are some specific rules about standing.However, due to the relevance of what has been developed in the American legal system about this issue, essentially from class actions and Rule 23, it is necessary to discuss exact questions about standing to sue and adequacy on what concerns, specifically, to the necessity that an adequate representative of a class proves injury in fact to be so considered. Related to the Brazilian legal system, it is necessary to keep in mind that national legislator determines who have standing to class jurisdiction ope legis. Among them there are associations, from which is required, in order for them to have standing: constitution one year prior to the class action filing before a court; authorization from their associates to the action; and, also, compatibility between the matter taken to court and objectives of the association. What is observed, nevertheless, is that national precedents give a broad interpretation to these requisites, in order to, correctly, avoid barriers to access to justice. Finally, it is worth mentioning that there are several practical questions about association standing in class actions, nonetheless what is effectively relevant about this issue is the impossibility to create barriers to this standing that, clearly, only makes concrete the corollary of access to justice, so important to a Democratic State of Law